PENERAPAN STRATEGI METAKOGNITIF PADA MATA KULIAH KAJIAN MATEMATIKA SD UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PGSD - Annisa, Choirul (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2015)
During the learning process of Kajian Matematika SD, there are only 10-15% of students who ask questions or give opinions. Students will express his opinion only when teacher raised questions. Writing test results also show that students are still cannâ??t collecting the necessary information, give reasons and solve the problem. This indicates that the critical thinking skill of students still needs to be improved. Metacognition is awareness in using strategies in the learning process so they can actively learning, critical thinking, able to solve problems and make decisions. Metacognitive strategy that consist of planning, monitoring and evaluating can be used to develop the skill of metacognitive. This research belongs to the classroom action research. The results of this research obtained that the implementation of metacognitive strategies is able to improve students's critical thinking skills.